2009
DOI: 10.1007/s11431-009-0270-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of magnetospheric ULF waves excited by positive and negative impulses of solar wind dynamic pressure

Abstract: The sources of ultra low frequency (ULF) waves in the magnetosphere are generally believed to be either the external solar wind perturbations or the internal plasma instabilities. When a sudden impulse of the solar wind dynamic pressure impinges on the magnetopause, ULF waves might be excited and thus the solar wind energy is transported into the earth's magnetosphere. In this paper, we study the ULF waves excited by different kinds of sudden solar wind pressure impulses through an MHD simulation. We primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…Solar wind dynamic pressure pulses that compress the magnetopause and launch fast mode waves can stimulate FLRs in the dayside magnetosphere around magnetic local noon . Numerical studies of ULF waves excited by solar wind impulses have confirmed coupling between global cavity modes and FLRs (Allan and Poulter 1992;Zhu et al 1991;Lee et al 1989;Zhang et al 2009). …”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Solar wind dynamic pressure pulses that compress the magnetopause and launch fast mode waves can stimulate FLRs in the dayside magnetosphere around magnetic local noon . Numerical studies of ULF waves excited by solar wind impulses have confirmed coupling between global cavity modes and FLRs (Allan and Poulter 1992;Zhu et al 1991;Lee et al 1989;Zhang et al 2009). …”
Section: Introductionmentioning
confidence: 90%
“…The main difference between these two ULF wave generation mechanisms is that solar wind dynamic pressure pulses interact with the entire bow shock, while HFAs interact with the bow shock locally and move parallel to the bow shock. The MHD simulation and observational studies by Zhang et al (2009Zhang et al ( , 2010b have shown that ULF waves are generated inside the magnetosphere by negative solar wind dynamic pressure pulses. However, the possible ULF wave generation by HFAs has not been fully explored.…”
Section: Ulf Waves Driven By the Transient Foreshock Phenomenamentioning
confidence: 99%
See 2 more Smart Citations
“…The magnetopause current is intensified when a positive impulse impinges on the Earth's magnetosphere. Furthermore, ULF waves are excited in the inner magnetosphere as a result of the interaction between the Earth's magnetic field and positive solar wind pressure impulses/interplanetary shocks [28,53,54]. Although many of the positive impulses of solar wind dynamic pressure are associated with shocks, other types of positive impulses are found to exist, e.g.…”
Section: Ulf Waves Excited By Both Positive and Negative Solar Wind Dmentioning
confidence: 99%